LOS INTERESES DE SARKOZY Y LAS TRIBULACIONES DE LA POLÃTICA FRANCESA HACIA LIBIA - Moreira, OnÃ©simo JuliÃ¡n (European Scientific Journal, ESJ, 2014)
The French foreign policy process that accompanied the birth of the Fifth Republic and the collapse of the colonial system was inspired by the idea of greatness (grandeur de La France). National pride in the exercise of foreign policy, operated for many years as a counterweight to the decline of its international position as a power. However, from De Gaulle to Chirac, French policy was able to get some achievements based on a design that combined the national interest with the idea of grandeur. Although some scholars argue that â€œthe foreign policy of no other Western state is driven by such narcissismâ€ (Muravchick, 2007), other studies focus on the particularities of the French political system and the concept of monochromatic presidential government (Elgie & Griggs, 2000), a system of government in which the president decides the contents of the policy and is responsible for their successes and failures. For the Mediterranean region, the policy of the governments of the Fifth Republic acted on broadly similar principles until Nicolas Sarkozy came to power. Therefore, this paper focuses on the changes that occurred in the French position towards the Mediterranean region during the presidential term of Sarkozy and stresses the presidentâ€™s unequivocal responsibility. Furthermore, the article emphasizes the direct engagement of France during the events in Libya in 2011 as the result of a personal interest rather than a foreign policy design.